First record far Europe ofBradinothrips musae (Hood) (Thysanoptera Thripidae ) (Bollettino di zoologia agraria e bachicoltura, 2024)
Bradinothrips musae (Hood), a new thrip for European fauna, is recorded. It has been collected in a greenhouse near Bergamo (Lombardy) on Spathiphyllum sp. coming from Costa Rica.
Keywords: Bradinothrips musae; Thripidae; European fauna; Spathiphyllum